2017
DOI: 10.3390/app7090915
|View full text |Cite
|
Sign up to set email alerts
|

Ultrashort Free-Electron Laser X-ray Pulses

Abstract: For the investigation of processes happening on the time scale of the motion of bound electrons, well-controlled X-ray pulses with durations in the few-femtosecond and even sub-femtosecond range are a necessary prerequisite. Novel free-electron lasers sources provide these ultrashort, high-brightness X-ray pulses, but their unique aspects open up concomitant challenges for their characterization on a suitable time scale. In this review paper we describe progress and results of recent work on ultrafast pulse ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 120 publications
1
34
0
Order By: Relevance
“…In figure 4(c), one can see considerable change of the LFPAD, for the molecules aligned parallel to the polarization vector, from those in figures 4(a) and (b). This change is reasonably reproduced by the simulated LFPAD according to equation (4), which is the average of the MFPAD over the molecular orientation, as can be seen in the figure.…”
Section: Photoelectron Angular Distributions From Aligned Cosupporting
confidence: 56%
See 2 more Smart Citations
“…In figure 4(c), one can see considerable change of the LFPAD, for the molecules aligned parallel to the polarization vector, from those in figures 4(a) and (b). This change is reasonably reproduced by the simulated LFPAD according to equation (4), which is the average of the MFPAD over the molecular orientation, as can be seen in the figure.…”
Section: Photoelectron Angular Distributions From Aligned Cosupporting
confidence: 56%
“…Recent developments of x-ray free electron lasers (XFELs) [1][2][3][4] and table-top laser sources [5] are bringing off ultrafast imaging of molecules with femtosecond temporal and sub-Ångstrom spatial resolutions [6][7][8][9]. The first imaging of atomic motions during photochemical processes has been achieved by the ultrafast electron diffraction (UED) [10][11][12] and the ultrafast x-ray diffraction (UXD) [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the interested reader, a comprehensive review of x-ray FEL pulse characterization techniques can be found in [33]. Otherwise, it should be emphasized that the novel aspect of the current work is not in x-ray diagnostics.…”
mentioning
confidence: 99%
“…The present issue also includes XFEL-pulse characterizations and instrumentations. Helml et al review the progress on ultrashort pulse characterization of XEFLs [9], while Inbushi et al…”
mentioning
confidence: 99%